Follicular Fluid Levels of Adrenomedullin 2, Vascular Endothelial Growth Factor and its Soluble Receptors Are Associated with Ovarian Response during ART Cycles - Ranjbaran, Ali; Nejabati, Hamid Reza; Ghasemnejad, Tohid; Latifi, Zeinab; Hamdi, Kobra; Hajipour, Hamed; Raffel, Nathalie; Bahrami-Asl, Zahra; Hakimi, Parvin; Mihanfar, Aynaz; Nouri, Mohammad; Fattahi, Amir (Geburtshilfe und Frauenheilkunde, 2019)
Introduction Adrenomedullin 2 (ADM2) and vascular endothelial growth factor (VEGF) affect ovarian function, especially angiogenesis and follicular development. The actions of VEGF can be antagonized by its soluble receptors, soluble Fms-like tyrosine kinase-1 (sFlt-1) and soluble VEGF receptor 2 (sVEGFR-2), as they decrease its free form. In the present study, we evaluated the relationship between follicular fluid (FF) levels of AMD2, VEGF and its soluble receptors, and ICSI outcomes. Materials and Methods ICSI cycle outcomes were evaluated and FF levels of VEGF, sFlt-1, sVEGFR-2 and ADM2 were determined using ELISA kits. Results FF levels of ADM2, VEGF, and sVEGFR-2 were significantly higher in non-responders compared to other ovarian response groups (p < 0.05). There were significant correlations between ADM2, VEGF and sVEGFR-2 levels as well as VEGF/sFlt-1 and VEGF/sVEGFR-2 ratios (r = 0.586, 0.482, 0.260, and -0.366, respectively). Based on the ROC curve, the cutoff value for ADM2 as a non-responder predictor was 348.55 (pg/ml) with a sensitivity of 67.7% and a specificity of 94.6%. Conclusions For the first time we measured FF ADM2 levels to determine the relationship to VEGF and its soluble receptors. We suggest that ADM2 could be a potential predictive marker for non-responders. Although the exact function of ADM2 in ovarian angiogenesis is not yet understood, our study may shed light on the possible role of ADM2 in folliculogenesis and ovulation.
CRIS-Team Scopus Importer:2019-05-14
Keywords: adrenomedullin 2; follicular fluid; ICSI; sFlt-1; vascular endothelial growth factor